Circulating Endocannabinoids: From Whence Do They Come and Where are They Going? - Hillard, Cecilia J (Neuropsychopharmacology, 2018)
The goal of this review is to summarize studies in which concentrations of circulating endocannabinoids in humans have been examined in relationship to physiological measurements and pathological status. The roles of endocannabinoids in the regulation of energy intake and storage have been well studied and the data obtained consistently support the hypothesis that endocannabinoid signaling is associated with increased consumption and storage of energy. Physical exercise mobilizes endocannabinoids, which could contribute to refilling of energy stores and also to the analgesic and mood-elevating effects of exercise. Circulating concentrations of 2-arachidonoylglycerol are very significantly circadian and dysregulated when sleep is disrupted. Other conditions under which circulating endocannabinoids are altered include inflammation and pain. A second important role for endocannabinoid signaling is to restore homeostasis following stress. Circulating endocannabinoids are stress-responsive and there is evidence that their concentrations are altered in disorders associated with excessive stress, including post-traumatic stress disorder. Although determination of circulating endocannabinoids can provide important information about the state of endocannabinoid signaling and thus allow for hypotheses to be defined and tested, the large number of physiological factors that contribute to their circulating concentrations makes it difficult to use them in isolation as a biomarker for a specific disorder.